2013
DOI: 10.1162/jocn_a_00339
|View full text |Cite
|
Sign up to set email alerts
|

The Biology of Linguistic Expression Impacts Neural Correlates for Spatial Language

Abstract: Biological differences between signed and spoken languages may be most evident in the expression of spatial information. PET was used to investigate the neural substrates supporting the production of spatial language in American Sign Language as expressed by classifier constructions, in which handshape indicates object type and the location/motion of the hand iconically depicts the location/motion of a referent object. Deaf native signers performed a picture description task in which they overtly named objects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 63 publications
2
43
0
Order By: Relevance
“…Finally, the fact that greater activation in the spatial language conditions also extended to superior occipital regions further supports the interpretation of these activations as reflecting mental imagery. Our finding of greater precuneus activation are similar to those of Emmorey and colleagues (2005, 2013) with ASL users, and show that these findings were not just a reflection of the visual-spatial modality of ASL, but a more general reflection of spatial language processing in general. Additionally, Wallentin et al (2006, 2008) found bilateral precuneus activation in spatial recall tasks, taxing spatial working memory and imagery of spatial relations.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Finally, the fact that greater activation in the spatial language conditions also extended to superior occipital regions further supports the interpretation of these activations as reflecting mental imagery. Our finding of greater precuneus activation are similar to those of Emmorey and colleagues (2005, 2013) with ASL users, and show that these findings were not just a reflection of the visual-spatial modality of ASL, but a more general reflection of spatial language processing in general. Additionally, Wallentin et al (2006, 2008) found bilateral precuneus activation in spatial recall tasks, taxing spatial working memory and imagery of spatial relations.…”
Section: Discussionsupporting
confidence: 79%
“…The superior parietal cortex in general has been associated with the manipulation of information in working memory (Koenigs, Barbey, Postle, & Grafman, 2009), processing of spatial relationships in both American and British Sign Language (Emmorey et al, 2005; MacSweeney et al, 2002), and spatial attention in general (Corbetta, Miezin, Shulman, & Petersen, 1993). The SPL, in particular, has been associated with a number of functions related to spatial attention, such as shifting spatial attention (Molenberghs, Mesulam, Peeters, & Vandenberghe, 2007), the communication of location and spatial classifiers in ASL (Emmorey et al, 2002; 2005; 2013), maintaining an internal representation of body position (Wolpert, Goodbody, & Husain, 1998), integrating audiovisual information (Molholm et al, 2006), coordinating actions in space (Segal & Petrides, 2012), completion of spatial mental tasks, such as mental mazes (Jerde et al, 2008), keeping track of referents in discourse (Almor et al, 2007), and the representation and processing of plural entities in language comprehension (Boiteau, Bowers, Nair, & Almor, 2014). The varied functions of the SPL in spatial attentional processes are of particular interest to the present study, which was primarily a study of language, not of spatial attention.…”
Section: Discussionmentioning
confidence: 99%
“…Although verbs of motion with classifiers occur in some spoken languages, in ASL these constructions are often iconic-the forms of the morphemes are frequently similar to the visual-spatial meanings they expressand they have therefore become a focus of discussion about the degree to which they (and other parts of ASL) are linguistic or gestural in character. Some researchers have argued that the features of motion and spatial relationships marked in ASL verbs of motion are in fact not linguistic morphemes but are based on the analog imagery system that underlies nonlinguistic visual-spatial processing (3)(4)(5). In contrast, Supalla (2, 6, 7) and others have argued that these ASL constructions are linguistic in nature, differing from gestures in that they have segmental structure, are produced and perceived in a discrete categorical (rather than analog) manner, and are governed by morphological and syntactic regularities found in other languages of the world.…”
mentioning
confidence: 99%
“…During both comprehension and production of spatial relationships in sign language, the superior parietal lobule (SPL) is activated bilaterally (4,5,12). In contrast, parallel studies in spoken languages have found no (12) or only left (20) parietal activation when people describe spatial relationships.…”
mentioning
confidence: 99%
See 1 more Smart Citation